2021
DOI: 10.3389/fnhum.2021.636191
|View full text |Cite
|
Sign up to set email alerts
|

Decoding Multiple Sound-Categories in the Auditory Cortex by Neural Networks: An fNIRS Study

Abstract: This study aims to decode the hemodynamic responses (HRs) evoked by multiple sound-categories using functional near-infrared spectroscopy (fNIRS). The six different sounds were given as stimuli (English, non-English, annoying, nature, music, and gunshot). The oxy-hemoglobin (HbO) concentration changes are measured in both hemispheres of the auditory cortex while 18 healthy subjects listen to 10-s blocks of six sound-categories. Long short-term memory (LSTM) networks were used as a classifier. The classificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…Furthermore, a t -test was applied to student participants. This test checks the statistical significance of the attained results [ 54 ]. The confidence interval is specified at 95% ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a t -test was applied to student participants. This test checks the statistical significance of the attained results [ 54 ]. The confidence interval is specified at 95% ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The output from the second layer is 12 × 128. Subsequently, the global average pooling is applied between the output layer for which the Adam optimization method was deployed [ 53 , 54 ].…”
Section: Feature Extraction and Classification Of Motion Intention Si...mentioning
confidence: 99%
“…Further work extended use of fNIRS to capture the hemodynamic response to sound in auditory cortex in children and infants. 95 96 97 Differential activations to various sound categories in auditory cortex have also been confirmed using fNIRS, 98 99 indicating that while fNIRS has lower spatial resolution than fMRI, it can be quite sensitive to changes in the type of sound stimulus being used. To our knowledge, no study to date has confirmed whether fNIRS has the necessary sensitivity for tonotopic mapping of the auditory cortex.…”
Section: Introduction To Functional Near-infrared Spectroscopymentioning
confidence: 83%
“…For classification tasks, the cross-entropy loss function 27 measures the difference in the probability distributions between ground truths and network predictions. Multiclass classifications 28 31 use categorical cross-entropy as the loss function, whereas binary classification problems use binary cross-entropy. For regression 32 or reconstruction 33 problems, the mean squared error loss function is used.…”
Section: Deep Learning Methodologymentioning
confidence: 99%